Vocational High School Students’ Problems in Writing Procedural Text of Manual Instruction - Manfaluthi, Muhamad Dedi Manfaluthi; Rudi Hartono; Abdurrachman Faridi (English Education Journal, 2024)
This study focused on investigating the problems of vocational high school students in writing the procedural text of manual instruction. This study described the kinds of problems that the students have faced to improve their writing competence. The study used qualitative as the approach and case study as its research design. The subjects of this study were five Vocational High School Students, 11th-grade students of Marketing Major in Cirebon. To collect the data, the writer used an open-ended questionnaire, interview and test. The data analysis was conducted in several ways. The data from the questionnaire were analyzed in several steps, there are coding, analyzing and interpreting. Then, the data from the interview were transcribed and the data from the test were analyzed qualitatively. The result of the study showed that the first was lack of discourse study understanding, it was the highest percentage was 56 % from analyzed data questionnaire, such as generic structure, linguistic features and sociocultural value of the text. The second was a lack of practice in writing activities with their English teachers was the middle percentage was 25% from analyzed data questionnaire, and the third was the lack of students’ confident and awareness was 19% from the respondents. The conclusion of the study stated that teaching writing in Vocational High Schools must be customized to the specific purposes and social contextualized text. The benefit of the research was that students were guided to write what they practice in the future as they need it.